Multi-objective reliability-redundancy allocation problem using particle swarm optimization - Garg, Harish; Sharma, S.P. (Computers & industrial engineering, 2013)
► We present a multi-objective reliability-redundancy allocation problem. ► Linear and nonlinear membership functions are used for defining their fuzzy goals. ► Preferences of DM corresponding to each objective has been incorporated in the objectives. ► We utilize the PSO algorithm to solve the optimization problem. ► The proposed method is validated through a real case study. This paper considers the multi-objective reliability redundancy allocation problem of a series system where the reliability of the system and the corresponding designing cost are considered as two different objectives. Due to non-stochastic uncertain and conflicting factors it is difficult to reduce the cost of the system and improve the reliability of the system simultaneously. In such situations, the decision making is difficult, and the presence of multi-objectives gives rise to multi-objective optimization problem (MOOP), which leads to Pareto optimal solutions instead of a single optimal solution. However in order to make the model more flexible and adaptable to human decision process, the optimization model can be expressed as fuzzy nonlinear programming problems with fuzzy numbers. Thus in a fuzzy environment, a fuzzy multi-objective optimization problem (FMOOP) is formulated from the original crisp optimization problem. In order to solve the resultant problem, a crisp optimization problem is reformulated from FMOOP by taking into account the preference of decision maker regarding cost and reliability goals and then particle swarm optimization is applied to solve the resulting fuzzified MOOP under a number of constraints. The approach has been demonstrated through the case study of a pharmaceutical plant situated in the northern part of India.